MiR‐181b promotes cell proliferation and reduces apoptosis by repressing the expression of adenylyl cyclase 9 (AC9) in cervical cancer cells. Issue 1 (20th November 2013) - Yang, Lei; Wang, Yan-Li; Liu, Shang; Zhang, Pei-Pei; Chen, Zheng; Liu, Min; Tang, Hua
Abstract : MicroRNAs are a class of small, endogenous, non‐coding RNAs that function as post‐transcriptional regulators. In this study, we found that miR‐181b promoted cell proliferation and inhibited cell apoptosis in cervical cancer cells. And we validated a new miR‐181b target gene, adenylyl cyclase 9 (AC9). miR‐181b restricted cAMP production by post‐transcriptionally downregulating AC9 expression. Phenotypic experiments indicated that miR‐181b and AC9 exerted opposite effects on cell proliferation and apoptosis. Abstract : miR‐181b promotes cell proliferation and suppresses apoptosis in cervical cancer cell lines. Adenylyl cyclase 9 (AC9) transcript is a direct target of miR‐181b. Knockdown of AC9 increases cell proliferation and decreases apoptosis in cervical cancer cell lines. miR‐181b is upregulated in cervical cancer tissues.